Mechanical properties and durability performance of concrete with dimension limestone waste as partial replacement for fine aggregates - Panganiban, Jasmin M. (Animo Repository, 2022)
The perpetually increasing demand for construction materials and its adverse impact to environment becomes a great challenge to many researchers. As the construction industry push towards sustainability, it is imperative to minimize the environmental burdens brought by construction materials, particularly in term of resource consumption as well as pollutants and waste generation. Quarrying and production of dimension limestone produced a considerable amount of solid and slurry waste, which has great potential to be used as alternative material in concrete. This research aimed to assess the mechanical properties and durability performance of concrete made with dimension limestone waste (DLW) as fine aggregate replacement. The experiments were conducted on concrete mixtures with DLW replacements of 0%, 20%, 40% and 60%. The investigation included test for compressive strength, flexural strength, splitting-tensile strength, sorptivity and resistance to sulfate attack. The strength test result shows the increases in compressive, flexural and splitting-tensile strength when DLW is added in the mixture. Furthermore, test results reveals that incorporation of DLW as sand replacement reduces the permeability of concrete and increases its sulfate resistance. Through response surface methodology, experimental data was utilized to develop a quadratic model to predict compressive, flexural and splitting-tensile strength. An optimum condition was modeled under 36% DLW content at curing age of 26.4 days corresponding to 24.07MPa, 6.65MPa, and 3.48MPa for compressive strength, flexural strength and splitting-tensile strength, respectively. The predictive models have been validated and a good correlation was observed between the predicted and experimental values judging from the t-test p-values obtained (<0.05). Based on the findings of this study, it has been concluded that replacement of sand by up to 36% DLW can result to concrete having optimum strength performance without any detrimental effect on workability and durability.